Tildrakizumab efficacy and safety in patients with psoriasis and concomitant metabolic syndrome: post hoc analysis of 5‐year data from reSURFACE 1 and reSURFACE 2. (25th June 2022) - Fernandez, A.P.; Dauden, E.; Gerdes, S.; Lebwohl, M.G.; Menter, M.A.; Leonardi, C.L.; Gooderham, M.; Gebauer, K.; Tada, Y.; Lacour, J.P.; Bianchi, L.; Egeberg, A.; et al.
Abstract: Background: Limited data are available on long‐term efficacy and safety of biologics in patients with psoriasis and metabolic syndrome (MetS), a common comorbidity. Objectives: This analysis updates tildrakizumab efficacy and safety for up to 5 years in patients with and without MetS. Methods: This was a post hoc analysis of the double‐blind, randomized, placebo‐controlled, phase 3 reSURFACE 1 (NCT01722331) and reSURFACE 2 (NCT01729754) trials in adult patients with moderate to severe chronic plaque psoriasis. Analyses included data through Week 244 from patients who continuously received tildrakizumab 100 (TIL100) or 200 mg (TIL200) and entered the extension studies, stratified by baseline MetS status. Efficacy was assessed via Psoriasis Area and Severity Index (PASI) scores. Safety was evaluated from exposure‐adjusted incidence rates (EAIRs) of treatment‐emergent adverse events (TEAEs). Results: reSURFACE 1 and reSURFACE 2 analyses included 26 and 44 TIL100‐treated patients with MetS, 98 and 167 TIL100‐treated patients without MetS, 34 and 30 TIL200‐treated patients with MetS, and 111 and 130 TIL200‐treated patients without MetS, respectively. There were no clinically relevant differences in PASI 75/90/100 response rates at Week 244 between patients with vs without MetS. The proportion of patients with vs without MetS achieving absolute PASI score <3 at Week 244 was 53.8% vs 69.4% and 77.3% vs 80.8% in reSURFACE 1 and 2, respectively, for TIL100‐treated patients and 58.8% vs 72.1% and 63.3% vs 72.3%, respectively, for TIL200‐treated patients. In both studies, median reduction from baseline PASI score at all time points in patients with vs without MetS was >83% vs >89% for TIL100 and >85% vs >90% for TIL200. Pooled EAIRs of TEAEs, serious TEAEs, and TEAEs of special interest were similar in patients with and without MetS. Conclusions: Tildrakizumab maintains efficacy and a favorable safety profile over 5 years in patients with psoriasis regardless of MetS status.